Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702430
|View full text |Cite
|
Sign up to set email alerts
|

"My Hand Doesn't Listen to Me!"

Abstract: Adoption and use of novel technology by the institutionalized 'oldest old' (80+) is understudied. This population is the fastest growing demographic group in developed countries, providing design opportunities and challenges for HCI. Since the recruitment of oldest old people is challenging, research tends to focus on older adults (65+) and their use of and attitudes towards existing communication technologies, or on their caregivers and social ties. Our study deployed a novel communication appliance among fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(23 citation statements)
references
References 31 publications
(41 reference statements)
0
23
0
Order By: Relevance
“…For six participants, those who had relatives living abroad or afar, their social connectedness -which is more than social interaction, it is meaningful social interactionincreased with InTouch. However, for two of our participants, the technology had the potential to make them more aware of their social isolation and loneliness as relatives and friends did not reply to their messages (Neves et al, 2015;Neves et al, 2017a;Neves et al, 2017b).…”
Section: Applicationsmentioning
confidence: 93%
See 1 more Smart Citation
“…For six participants, those who had relatives living abroad or afar, their social connectedness -which is more than social interaction, it is meaningful social interactionincreased with InTouch. However, for two of our participants, the technology had the potential to make them more aware of their social isolation and loneliness as relatives and friends did not reply to their messages (Neves et al, 2015;Neves et al, 2017a;Neves et al, 2017b).…”
Section: Applicationsmentioning
confidence: 93%
“…To test adoption and use of this app, as well as its potential to address issues of social isolation and loneliness, we conducted two-and three-month deployments of the technology in a long-term care facility and a multi-care retirement community in Toronto, Canada (Neves et al, 2015;Neves et al, 2017a;Neves et al, 2017b). These studies included 16 older adults (ages ranged from 74 to 95; M = 83.9; SD = 5.5; ten identified as female and six as male) and their study partners (relatives or friends).…”
Section: Applicationsmentioning
confidence: 99%
“…Privacy and context of use. The context of use should be carefully considered when designing multimodal technology (Neves et al 2015;Brewster 2010a, 2010b):…”
Section: Diverse Abilitiesmentioning
confidence: 99%
“…This might be true for some combinations of multimodal channels. For example, it has been shown that older adults find some modalities or combination of modalities too complex to use when using multimodal applications (Neves et al 2015;Naumann, Wechsung, and Hurtienne 2010;Lepicard and Vigouroux 2012). On the other hand, designing interaction with simplicity in mind might force a compromise on functionality (Norman 2010), and this holds true also for multimodal interaction.…”
Section: Design Trade-offs In Multimodal Interaction Design For Older Adultsmentioning
confidence: 99%
“…As a result, even though smartphone ownership among older adults has significantly increased in recent years [2, 3,12], smartphone adoption level for is still low (e.g., smartphone ownership in the US is at 27% for older adults as of 2015, whereas 85% of young people aged 18-29 are smartphone owners [13]). Consequently, older adults may be losing the possible benefits and opportunities from this growing digital era [1,5,7].…”
Section: Introductionmentioning
confidence: 99%